2007
DOI: 10.1055/s-2006-959333
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Algorithm for Anterior Skull Base Reconstruction after Oncological Resections

Abstract: Objective: To present our method for anterior skull base reconstruction after oncological resections. Methods: One hundred nine patients who had undergone 120 anterior skull base resections of tumors (52 malignant [43%], 68 benign [57%]) via the subcranial approach were studied. Limited dural defects were closed primarily or reconstructed using a temporalis fascia. Large anterior skull base defects were reconstructed by a double-layer fascia lata graft. A split calvarial bone graft, posterior frontal sinus wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 20 publications
2
126
1
3
Order By: Relevance
“…In contrast, the STV lies just beneath the skin and is easily affected by previous operations and scar formation. Gil et al 16 have suggested that the difficulty and complexity of skull-base reconstruction are due, in part, to the high frequency of previous operations. An advantage of using the MTV is that it appears to overcome these problems.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the STV lies just beneath the skin and is easily affected by previous operations and scar formation. Gil et al 16 have suggested that the difficulty and complexity of skull-base reconstruction are due, in part, to the high frequency of previous operations. An advantage of using the MTV is that it appears to overcome these problems.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the literature, the purposes of the reconstruction in present case were to cover the bone, to achieve the separation of the cranial cavity from the nasopharynx, the paranasal sinuses, and the orbit, to achieve the watertight dural reconstruction and to provide an adequate support of the brain tissue [3][4][5][6]. The available options to reconstruct the frontal bone include autogenous bone graft (particularly split-thickness calvarial bone grafts) [7], alloplastic materials (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…The options to reconstruct the dural include free autografts (e.g. fascia lata and temporalis fascia) and vascularized flaps (i.e., free muscular flaps, pericranial or galeal flaps), assuming that an overlying vascular tissue will provide the long-term viability of the fascial graft [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Yine oral kavitenin cilt tutulumu yapmış tümörlerinde hem cilt hem de oral kavite rekonstrüksiyonu yapılması gerektiğinden mutlak MSDF endikasyonu vardır (Şekil 3a-d); bu endikasyon ile mandibula ve cilt tutulumu olan hastalarda çalışmamızda eş zamanlı FF ve RÖKF, kemik defekti olmayan hastalarda ise RÖKF kullanıldı. Maksillofasiyal rezeksiyonlar sonrası geniş ön kafa kaidesi defekti oluşan durumlarda dura ve intrakraniyal dokuların izolasyonu için bölgenin vaskülarize doku ile proteksiyonu gerekir, [13] bunun için RÖKF ve RAF literatürde en çok kullanılan MSDF tipleridir, bizim çalışmamızda ise bu endikasyon ile üç hastada RAF kullanıldı. Farenksin total çıkartıldığı ve sirküler tarzda farenks defekti olan ileri evreli hipofarenks tümörlerinde de tüp şeklinde neofarenks oluş-turulması gerekir.…”
Section: Discussionunclassified